Study on the Application of the Moroccan Concept at Naima Resto in Bandung - Rifa’Nur Fadhilah (JOMANTARA, 2026)
Moroccan design is known for its distinctive styling characterized by rich ornamentation, geometric patterns, contrasting color schemes, and various combinations of traditional elements with a warm, exotic, yet elegant atmosphere. This study aims to analyze the extent to which Moroccan elements are present in the café and how they influence visitors' spatial experience. The research method uses a descriptive qualitative approach with field observation techniques, visual documentation, and literature studies on the characteristics of Moroccan interior design. The results of this study indicate that the Moroccan concept applied at Café Nayma is reflected in the use of mosaic patterns, wooden carvings, textured ethnic fabrics, and warm-colored lighting that supports a relaxed and aesthetic atmosphere. Furthermore, the integration of local Bandung elements adds contextual value without diminishing the original cultural nuance. The conclusion of this study asserts that Moroccan-concept interior design can serve as an inspiration in creating a unique and characterful space identity, while also enhancing the attractiveness and comfort for visitors.